IBUPROFEN IN PAIN TREATMENT IN CHILDREN - R. V. Denisova ("Paediatrician" Publishers LLC, 2012)
The article contains results of therapeutic efficacy of ibuprofen in pain syndrome management in children. Validity of its use is doubtless. Analgesic effect of Ibuprofen has been confirmed in clinical trials in patients with migraine and ENT-disorders. In this article we also review international experience of ibuprofen use in juvenile arthritis..